Di Bawah Payung Habib: Sejarah, Ritual, Dan Politik Tarekat Syattariyah Di Pantai Barat Aceh - Sehat Ihsan Shadiqin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2017)
This article looks at the development of Sufism in the form of Sufi orders (tarekat) in contemporary Aceh, notably Syattariah order (Tarekat Syattariyah). Syattariah order has a strong foundation in the history of Islam in Aceh. A great Acehnese scholar, Abdurrauf As-Singkili is the figure who spread this order in the archipelago. One of the centers of the development of the Syattariyah order in contemporary Aceh is Nagan Raya with Habib Muda Seunagan as the main leader. Syattariah grows rapidly under his influence by forming a special formula that is very preferential to the local culture. His role is evident in the term